Project management in libraries, archives and museums : working with government and other external partners - Carpenter, Julie, 1952- (Chandos information professional series., 2011)
Aimed at practitioners and managers, this practical handbook provides a source of guidance on project management techniques for the academic and cultural heritage sectors, focusing on managing projects involving public sector and other external partners. Issues under consideration and illustration include: different approaches to managing projects and how to select appropriate methods; using project management tools and other applications in project development and implementation; ensuring the sustainability of project outcomes and transferability into practice; realistic monitoring methodologies and specification and commissioning evaluation work that has real value.